Application of Transtheoretical Model on Behavioral Changes, and Amount of Physical Activity Among University’s Students - Kien Ting Liu; Yee Cheng Kueh; Wan Nor Arifin; Youngho Kim; Garry Kuan (Frontiers in Psychology, 2018)
This study’s purpose was to examine the structural relationship of the transtheoretical model (TTM) and the amount of physical activity (PA) among undergraduate students in health and medicine at Universiti Sains Malaysia. A cross-sectional study was carried out among students who took part in the co-curricular program. Co-curricular program includes activities that take place outside of the regular lectures or tutorials in the University. Students recruited through purposive sampling were informed that their participation was entirely voluntarily. Those interested completed the self-administered questionnaire, which consisted of the decisional balance, processes of change, self-efficacy, stages of change scales, and Godin leisure-time exercise questionnaire. Data were analyzed using Mplus version 8 for descriptive statistics and structural equation modeling analysis for inferential statistics. A total of 562 students participated in the study. The majority of the students was female (79.0%) and Malay (73.3%) and average of exercise sessions per week was 2.62, with a mean of 43.37 min per exercise session. The final structural model fit the data well based on several fit indices (SRMR = 0.046, RMSEA (CI: 90%) = 0.061 (0.045, 0.078), RMSEA p = 0.130). The model showed that stages of change significantly affected self-efficacy (p < 0.001), pros (benefits of exercise; p < 0.001), cons (barriers to exercise; p = 0.022), and processes of change (p < 0.001). The model also showed significant inter-relationships among the TTM constructs and supported seven hypotheses. Among all the variables examined, only processes of change significantly affected PA (p < 0.001). However, stages of change (p < 0.001) and pros (p =< 0.001) had significant indirect effects on PA via processes of change. The findings support that individuals’ stages of change affect their self-efficacy level, or the ability to make positive and negative decisions and perform behavior accordingly. The study confirms that making correct decisions and taking action accordingly can increase PA levels.